Implementation of Student Management in Improving the Quality of SDIT Ummatan Wahidah, Rejang Lebong Regency - Irwan Fathurrochman (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2022)
In madrasah, student management can be a place to raise standards and performance. In order for educational institutions to measure the success of student achievement, students are properly supervised. Student management is an initiative to manage children from the time they start school until they graduate. Planning, mentoring, evaluation, and transfer are student management tasks that must be completed before graduation. The purpose of this study was to find out how the management of students at SDIT Ummatan Wahidah. The research methodology is a qualitative research method with a phenomenon-oriented approach in conducting research. information was collected through observation, interviews, and documentation studies. The findings of the study indicate that SDIT Ummatan Wahidah was established for 10 years creating outstanding students with the concept of student management at SDIT Ummatan Wahidah through student planning activities, student development, student evaluation, and transfers.